Fresh versus frozen blastocyst transfer outcomes deriven from the same ICSI cycle in male factor infertility - Seda Karabulut; Pelin Kutlu; Oya Korkmaz; M. Volkan Bülbül; İlknur Keskin (Clinical and Experimental Obstetrics & Gynecology, 2021)
The aim of this study was to investigate the clinical outcomes of fresh and frozen-thawed blastocyst transfer deriven from the same ICSI cycle because of male infertility. 2372 couples undergoing a total of 5075 ICSI cycles (2372 fresh + 2703 frozen embryo transfer) were enrolled in the study. Female factor infertility cases were excluded to prevent from the contribution of maternal factors that would influence the outcomes dramatically. Only the cycles for which day 5 blastocyst transfer was performed, had at least 1 surplus blastocyst available for freezing, and had at least one frozen embryo transfer (FET) cycle were included in the study. Clinical pregnancy rates and live birth rates were compared between fresh and FET cycles. No statistically significant difference was obtained in clinical pregnancy rates and live birth rates of fresh versus FET cycles of day 5 transfers, regardless of the number of embryos transferred. According to the results of the recent study, frozen embryo cycles appear to be as effective as fresh ICSI cycles provided that the patients’ embryos can develop into blastocysts, which is proven by using the same patient as the control group regardless of the result of previous ICSI attempt but further research is required to test the efficacy in terms of cost-effectiveness and the duration for conception.